Understanding Patient Anxieties in the Social Media Era: Qualitative Analysis and Natural Language Processing of an Online Male Infertility Community - Osadchiy, Vadim; Mills, Jesse Nelson; Eleswarapu, Sriram Venkata (JMIR Publications, 2020)
BackgroundCouples struggling with infertility are increasingly turning to the internet for infertility-related content and to connect with others. Most of the published data on infertility and the internet only address the experiences of women, with limited studies focusing exclusively on internet discussions on male factor infertility. ObjectiveThe aim of this study was to understand the concerns and experiences of discussants on an online male infertility community and to provide insight into their perceptions of interactions with health care professionals. MethodsUsing the large-scale data analytics tool BigQuery, we extracted all posts in the r/MaleInfertility community (877 members) of the social media website and discussion board Reddit from November 2017 to October 2018. We performed a qualitative thematic analysis and quantitative semantic analysis using Language Inquiry and Word Count 2015 of the extracted posts to identify dominant themes and subthemes of discussions. Descriptive statistics and semantic analytic Z-scores were computed. ResultsFrom the analysis of 97 posts, notable themes and subthemes emerged: 70 (72%) posts shared personal experiences, including feeling emasculated or isolated or describing a negative (28/97, 29%), positive (13/97, 13%), or neutral (56/97, 58%) experience with a health care professional; 19% (18/97) of the posts posed questions about personal semen analysis results. On the basis of semantic analysis, posts by men had higher authenticity scores (Z=3.44; P<.001), suggesting more honest or personal texts, but lower clout scores (Z=4.57; P<.001), suggesting a more tentative or anxious style of writing, compared with posts by women. ConclusionsTo our knowledge, this study represents the first evaluation of a social media community focused exclusively on male infertility using mixed methodology. These results suggest a role for physicians on social media to engage with patients and connect them to accurate resources, in addition to opportunities to improve in-office patient education.